Effect of Cellulose Nanofibers Concentration on Mechanical, Optical, and Barrier Properties of Gelatin-Based Edible Films [Efecto de la Concentración de Nanofibras de Celulosa Sobre Las Propiedades Mecánicas, Ópticas y de Barrera en Películas Comestibles de Gelatina] - Osorio-Lira, F (Universidad Nacional de Colombia, 2015)
The effect of gelatin, glycerol, and cellulose nanofiber (CNFs) concentrations on the mechanical properties, water vapor permeability, and color parameters of films was evaluated. The results indicate that the color is only affected by the gelatin concentration. Mechanical tests indicated that with increasing concentration of gelatin and CNFs, there is an increase in tensile strength, whereas an increase in glycerol concentration causes an increase in elongation, making the films more flexible. An increased concentration of gelatin and glycerol makes the film more permeable to water vapor, while an increase in the concentration of CNFs reduces this property. Finally, the addition of CNFs to gelatin-based films improves their mechanical and barrier properties (water vapor) without affecting the appearance (color) of the films. © The author.